Bibliography on English-speaking Quebec - O'Donnell, Brendan (2009)
This bibliography aims to help anyone studying English-speaking Quebec find material about the nature, history, contributions, and concerns of this diverse official language minority community. It reveals the wealth of available material and catalogues it in a useful way in the hope of stimulating further research on English-speaking Quebec. The bibliography contains secondary sources related to the study of English-speaking Quebec. It covers the period from the Conquest to the present day. Types of resources include everything from scholarly studies to magazine articles, by way of films and websites. Despite this, the bibliography does not claim to be exhaustive and excludes documents such as encyclopedia articles and entries in the Dictionary of Canadian Biography.... Website description